Analysis of monetary policy mechanism in Indonesia through interest rate channels on the stock market - Rifqah Pratiwi Siregar; Ahmad Albar Tanjung; M Syafii Syafii (Jurnal Mantik, 2023)
This study examines how the interest rate channel of the monetary policy mechanism affects the Indonesian stock market. This study also seeks to estimate the amplitude of factors inside the interest rate channel in reaction to stock market changes, namely the Indonesia Stock Exchange Composite Index (IHSG). This study uses the Vector Error Correction Model (VECM) regression model to determine how much the interest rate channel of the monetary policy transmission mechanism affects the Indonesian stock market (IHSG). This study uses monthly secondary data from 2015 to 2022. The Bank Indonesia website's yearly reports provided this study's secondary data. This study examined the impact of the interest rate channel as a monetary policy transmission mechanism on the stock market (IHSG) using the BI rate, interbank money market interest rate (PUAB), deposit rate, Covid-19, and composite stock price index. The effective interest rate channel shows that Indonesia's monetary policy mechanism affects the stock market (IHSG). This phenomena works immediately and long-term. Interest rate shocks altered IHSG responsiveness. However, the Indonesian Stock Exchange Composite Index (IHSG) is affected by deposit rates and Covid-19 conditions throughout time. Deposit rates affect interest rates and the Indonesian Stock Exchange Composite Index (IHSG).